PENGARUH INOVASI PRODUK DAN HARGA TERHADAP KEUNGGULAN BERSAING USAHA KARAWO DI KOTA GORONTALO - Hapsawati Taan (Jurnal Bisnis dan Kewirausahaan, 2017)
The purpose of the study is 1) To determine whether there is influence of product innovation on competitive advantage 2) to determine whether the effect of price on competitive advantage 3) to determine whether the effect of product innovation and price simultaneously towards excellence bersaing. Pendekatan is quantitative , Methods of data collection using questionnaires, observation and documentation. The population is karawo craft businesses in the city of Gorontalo. The sampling method proportional random sampling method by means of sampling simple random sampling. Data analysis using SPSS 16:00. Multiple regression analysis techniques. The results of this study indicate that 1) the product innovation have a significant effect on competitive advantage. 2) Price significant effect on competitive advantage. 3) Innovation products and prices influence simultaneously on competitive advantage. This is an indication that the innovation of products and good prices can increase the competitive advantage of businesses karawo in Gorontalo.